Evaluating the impact of the Minimization of Aggression and Violence (MoAV) intervention on mechanical restraint use in Qatar's acute mental health setting - Ananth Nazarene (21239912) (2025)
Background In inpatient psychiatric units, around 50 % of patients exhibit aggressive symptoms, with aggression and violence being common issues. While mechanical restraint is least preferred by patients and is considered a last resort by healthcare professionals, its use might be preventable. Minimization of Aggression and Violence (MoAV) intervention in acute mental health services offers a comprehensive assessment, comprehensive staff training in de-escalation, and the implementation of evidence-based, proactive, and non-invasive measures can help reduce the need for restraints. Aim To assess the impact of the MoAV intervention introduced in 2017 across acute inpatient mental health services, focusing on its effect on physical restraint incidents. A retrospective analysis compared data from 2016 (pre-intervention) and 2021 (post-intervention). Result There was a significant reduction in the number of restraints from 253 in 2016 to 47 in 2021. The percentage of restrained patients decreased from 25 % to 4 %, p = (<0.001). The mean duration of restraint incidents slightly increased from 59.1 min in 2016 to 61.3 min in 2021, though this change was not statistically significant. Conclusion Overall, the MoAV intervention appears to have made significant strides in reducing restraint use in acute mental health settings. Further research and continuous evaluation are essential to build on these findings and enhance patient care and safety. Other Information Published in: Archives of Psychiatric Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apnu.2025.151890